AICCRA I2G Open Innovation Challenge, Internship and Grant Opportunity Final Report - Banda, CT; Silwizya, D; Mwape, D; Makungwe, M; Pele, WK; Ngowenani, N; Muzungaire, L; Mutenje, MJ (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report provides a comprehensive analysis of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Internship Innovation Grant (I2G) Open Innovation Challenge (OIC), which was implemented by BongoHive. An Open Innovation Challenge (OIC) is a structured initiative that invites individuals and teams from various backgrounds to propose solutions to a specific problem or set of problems known as challenge statements. The OIC aimed to: enhance private sector engagement and awareness of CSA and CIS; foster the development of incremental or disruptive products and services; and facilitate student and youth engagement, as well as empowerment.